Utilisation of Local Penicillium SPP. In Consortium with Bacillus SPP. As Bioremediators for Shrimp Culture - Abd Karim, Murni Marlina (2008)
Shrimp aquaculture industry is suffering from severe disease outbreaks, environmental degradation and poor management practices. This project was undertaken to investigate the use of Penicillium isolates as bioremediation consortium with potential Bacillus spp. for economical and environmental-friendly clean-up of shrimp culture tank water, maintenance of good water quality, biocontrol against pathogenic vibrios and enhancement of shrimp production in shrimp hatchery with zero water exchange. Two potential Penicillium spp. S6 and S48 were originally isolated from sediment samples. S6 was collected from Sungai Dina while S48 was collected from Teluk Adang, Johor. The Penicillium isolates were identified up to genus level based on colony morphology and were coded as Penicillium sp. S6 and Penicillium sp. S48. The Penicillium species S6 and S48 showed no inhibitory effect towards B. pumilus, B. subtilis and B. licheniformis and no mycotoxins were detected when the isolates were run on thin-layer chromatography against vomitoxin, aflatoxin B1, B2, G1 and G2 standard. The S6 colony produced amylase enzymes while S48 produced four types of major extracellular enzymes viz., amylase, protease, lipase and gelatinase. In a preliminary biocontrol experiment using disc diffusion methods, S6 showed a significant inhibitory effect on the growth of the pathogenic vibrios tested. Both potential isolates passed the non-pathogenicity test against shrimp postlarvae (PL15). Preliminary ammonia reduction experiment showed that S6 in its mycelial form and S48 in the spore forms reduced the total ammonia nitrogen (TAN) concentration better in the flasks. A cocktail of microorganisms containing S6 and S48 could reduce ammonia significantly than other cocktails when combination of Penicillium spp. (S6 andS48) and Bacillus spp. was tested. Results revealed that a microorganism cocktail containing S6 reduced ammonia significantly higher (p<0.05) than other combination of isolates. Hatchery tanks containing PL 15 to 36 grown for 3 weeks and treated with combination of Penicillium spp. (S6 and S48) showed the highest survival rate (41.17%) compared to other treatments. The TAN concentration of the hatchery tank treated with a combination of Penicillium spp. (S6 and S48) with final concentration of 0.721 mgl-1 and tanks treated with Penicillium sp. S6 (final concentration 0.829 mgl-1) also showed significant reduction of TAN compared to control tanks (final concentration 2.153 mgl-1 ), at 21 days of growth. The PL grown in Penicillium sp. S6 tanks and microorganism cocktail tanks (Penicillium spp. and Bacillus spp.) showed better stress tolerance (90%) compared to other treatments and control tanks (67%). Vibrio counts were significantly lower in tanks treated with Bacillus spp. (p<0.05) compared to other treatments. In addition, the vibrio counts for tanks treated with Penicillium sp. S6 also shown significant reduction (p<0.05) and good specific growth rate (15.32%) compared to the control (11.41%). Results showed that selected Penicillium spp. satisfied the criteria to qualify as bioremediation agent in marine shrimp culture.